An Analysis of Profitability Ratios to Assess the Financial Performance of PT Mayora Indah Tbk - Lukman, Siti Diva Syarifah; Yusuf, ST. Nursaadah; Uksi, Rafika (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2026)
This study aims to analyze profitability ratios in assessing the financial performance of PT Mayora Indah Tbk during the 2023–2025 period. Profitability ratios are used to determine the company’s ability to generate profits through its sales, assets, and capital. This study employs a quantitative descriptive method utilizing secondary data in the form of PT Mayora Indah Tbk’s financial statements obtained from the company’s annual reports. The analysis was conducted using profitability ratios, specifically Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The results indicate that all profitability ratios declined during the study period. The NPM decreased from 10.30% to 7.52%, ROA decreased from 13.59% to 9.27%, and ROE decreased from 21.23% to 15.84%. This decline indicates that the increase in the company’s sales, assets, and equity has not been accompanied by an optimal increase in net profit. This situation was influenced by rising operating costs, cost of goods sold, and fluctuations in foreign exchange rates. Nevertheless, PT Mayora Indah Tbk was still able to maintain a fairly good level of profitability. Therefore, the company needs to improve operational efficiency and cost management to enhance its financial performance in the future.